Artificial intelligence in scientific research: Artificial intelligence in scientific research - Morales, Juan (2023)
For now, we cannot draw definitive conclusions; in the future, we will know the benefits or detriments of AI. Rather, it can be considered an opportunity to open lines of research, and only time will tell the impact of AI on research.